Welding parameter maps to help select power and energy consumption of friction stir welding. (June 2018) - Choi, WoongJo; Morrow, Justin D.; Pfefferkorn, Frank E.; Zinn, Michael R.
Abstract: The objectives of this work are to investigate power and energy consumption of friction stir welding over a wide range of welding parameters and to provide a welding parameter map synthesized with their relations to welding quality. Friction stir welding has been known as an energy efficient welding technology because the whole process takes place in the solid-state, i.e., no excessive heat is needed to melt the workpiece. However, the study of the energy consumption and resulting welding quality across a wide parameter window has not been established inclusively. In this work, a series of 6061-T6 aluminum butt welds were created by friction stir welding across various welding parameters (spindle speeds and weld speeds). In order to understand the overall power and energy consumption, both mechanical process power and electrical wall plug power were measured on the 3-axis CNC mill used to perform the welds. Additionally, temperatures near the workpiece surface and weld roots were measured. The resulting weld quality was assessed by conducting tensile tests of weld cross-sections to determine the location of failures. The results of the power/energy, temperatures, and tensile tests were incorporated, producing an inclusive welding parameter map. The welding parameter map helps identify minimum power and minimum energy consumption points within the process constraints needed for maintaining good welding quality. The general approach presented in this paper can be applied to different welding setups and conditions.